Enterostomal Therapy Service: Ten-year Experience at B.P. Koirala Memorial Cancer Hospital - Sharma, Sarojini; Subedi, Babita (Nepalese Journal of Cancer, 2019)
Introduction: Enterostomal therapy (ET) is the newly evolving subspecialty area of nursing. None of the university started the ET courses in Nepal. Very few ET nurses catering the needs of osteomates in different hospital. Increasing burden of colorectal and urinary bladder cancer increases the ostomy population. There are no definite data regarding the ostomy population in national context. So, this is the neglected area of care in most cancer hospital of Nepal. The objective of this study is to find out the total number of ostomy population in terms of types of ostomies, age, sex, geographical distribution, complications and stoma service availability at BP Koirala Memorial Cancer Hospital. Methods: A descriptive study was carried out retrospectively at, BP Koirala Memorial Cancer Hospital, Bharatpur Nepal and approved by nursing department. All available data were abstracted from stoma clinic from 2008 to 2018. Results: There were total 659 ostomates registered in the stoma clinic. Among them majority 63% were male. There were main three categories of ostomate namely colostomies (66.7%) 440, Ileostomies (9.8%) 65 and urostomies (23.3%) 154. Ostomate represented from 56 districts. International osteomate also took services from the clinic. Peristomal skin excoriation, Parastomal hernia, stoma prolapsed were complications reported by the osteomates. Conclusion. This aspect of ostomy care and management deserves an investment of research to find out the reliable data.